2008
DOI: 10.1093/sleep/31.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Selective 5HT2A and 5HT6 Receptor Antagonists Promote Sleep in Rats

Abstract: These results support a role for 5-HT2A receptor modulation in NREM sleep and suggest a previously unrecognized role for 5-HT6 receptors in sleep-wake regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 34 publications
(48 reference statements)
6
63
1
1
Order By: Relevance
“…The 5-HT2A receptor antagonist volinanserin MDL 100907 (MDL) increases sleep and decreases wakefulness in rats. In addition, Morairty et al have shown that 3 different doses of MDL increase sleep in general, as well as NREM sleep and delta sleep (57). The 5-HT2A receptor indirectly controls glutamatergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT2A receptor antagonist volinanserin MDL 100907 (MDL) increases sleep and decreases wakefulness in rats. In addition, Morairty et al have shown that 3 different doses of MDL increase sleep in general, as well as NREM sleep and delta sleep (57). The 5-HT2A receptor indirectly controls glutamatergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were recorded by telemetry (10,38,39); mice were recorded either by telemetry (40) or by tethered (10,21) procedures. State determinations and data analysis were conducted as described in these publications.…”
Section: Methodsmentioning
confidence: 99%
“…To monitor EEG/EMG activity, rats were implanted with sterile telemetry transmitters (F40-EET; Data Sciences, St Paul, MN) as described previously (Morairty et al, 2008(Morairty et al, , 2013 and detailed in Supplementary Materials.…”
Section: Surgical Proceduresmentioning
confidence: 99%